Intelligent reports for group decision support systems - Carneiro, João (2016)
The topic of Group Decision Support Systems (GDSS) is a not a recent one. In fact, it has been studied for the last three decades. In this work, we deal with the topic of Intelligent Reports in GDSS’ context. A defective interaction between the system and the decision-maker may lead to the complete failure of the GDSS. However, the study on how and which kind of information should be exposed to decision-makers is almost non-existent. Therefore, it is important to create reports adapted to the specific necessities of each decision-maker so that each one can acknowledge the advantage to use the system and feel motivated to do so. We believe that in this work, we approach important points that require special attention when developing Intelligent Reports. We navigate through all the important factors that affect decision-makers while making a decision. We detail each point and link them to all related questions and to which kind of structure an Intelligent Report should have in order to not compromise the success of the GDSS.